Race-based Traumatic Stress and Resilience: The Role of Spirituality Among Black Christians - Vazquez, Veola (Journal of psychology and theology, 2025)
Given the risks and negative outcomes associated with racism for people of color, in this study, we explored potential protective factors that might influence resilience among a community sample of 272 Black Christians. Specifically, we assessed the moderating role of several Christian experiences in the association between appraised stressfulness of racist experiences and the development of race-based traumatic stress (RBTS) symptoms. Results revealed that Christian gratitude, Christian worldview, Christian contentment, communion with God, and Black racial church composition all moderated the association between appraised discrimination-related stress and RBTS symptoms, with higher levels of each variable associated with lower levels of RBTS. Clinical and social implications of each Christian experience as a protective factor are discussed.